Demotivation Level and Demotivators Among EFL Students In Home Online English Learning During The Pandemic - Azza Nabila; Bambang Yudi Cahyono; Niamika El Khoiri (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2021)
This research is aimed at investigating the level of demotivation and the demotivating factors experienced by Indonesian EFL learners during home online English learning as response to social distancing order amid the COVID-19 pandemic. This research employed quantitative and qualitative data. Questionnaire with 27 items was the main instrument used to obtain data about learners’ level of demotivation and demotivators as well as to identify the frequency of each demotivator. An open-ended question was attached at the end of the questionnaire to dig other additional demotivators. An interview was also conducted to gain supporting data for in-depth analysis. The results showed that the level of the 198 students’ demotivation was 2.9, categorized as lowly demotivated. The most-frequently rated demotivators in home online English learning were lack of interaction with 78.9% responses followed by 66.2% for increasing assignments and 62.1% for slow Internet connection. In terms of content and material, expectation to use grammatically correct English was the most demotivating factor with 59.6% responses. The study also revealed additional demotivators namely unsupportive parents, doing house chores, and Wi-fi absence.